Pondok Pesantren Nurul Iman (Studi Tentang Sejarah Dan Kontribusinya Terhadap Masyarakat Desa Ujung Tanjung Pangkalan Balai Banyuasin III) - Lestari, Santi; Suriana, Sri (Tanjak: Sejarah dan Peradaban Islam, 2020)
The problem in this study is divided into 2 (two), namely: first, how is the history of the establishment of Nurul Iman Islamic boarding school. Second, what is the contribution of Nurul Iman Islamic boarding school to the community of Ujung Tanjung Pangkalan Village, Balai Banyuasin III. The purpose of this study was to find out how the history of the Nurul Iman Islamic Boarding School was founded and to find out what the contribution of Nurul Iman Islamic Boarding School to the Village Community of Ujung Tanjung Pangkalan Balai Banyuasin III. This research uses history and sociology. The use of a historical approach so that researchers try to reconstruct the past systematically and objectively, by collecting, evaluating, verifying, and synthesizing evidence to uphold facts and obtain strong conclusions. There are two sources of data used by the authors, namely primary data and secondary data.The results of research that have been carried out are the development of the Nurul Iman Islamic boarding school in Ujung Tanjung Village, which in its early days was still in a traditional form, then developed into an Islamic educational institution (Pesantren), this was marked by the establishment of the Nurul Iman Islamic Boarding School in 1960 AD. The contribution made by the Nurul Iman Islamic boarding school is divided into 3, namely: first, the economic sector: the Islamic boarding school cooperative, which also involves the community in Ujung Tanjung Village; second, the education sector: consisting of formal education and non-formal education; and third: the socio-religious field: majelis taklim and the art of reading Al-Qur'an.